Pengamalan Wasīlah Perspektif Al-Qur’an Surah Al-Maidah Ayat 35: Studi Kasus di Majelis Taklim Berkah Sekumpul Desa Lubuk Bayas Dusun IV - Khairi, Muhammad Alfi; Arifin, Zainal (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study is motivated by the phenomenon that the concept of Wasīlah is not only understood as a theological concept in Qur’anic exegesis but is also manifested in the religious practices of Muslim communities. This study aims to analyze the understanding and practice of the concept of Wasīlah from the perspective of the Qur’an, particularly Surah Al-Mā’idah verse 35, among the congregation of Majelis Taklim Berkah Sekumpul in Lubuk Bayas Village, Dusun IV. This research employs a qualitative approach with a field research design using the living Qur’an perspective. Data were collected through observation, in-depth interviews, and documentation involving the administrators and members of the religious study group. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing.The findings reveal that the congregation of Majelis Taklim Berkah Sekumpul understands Wasīlah as a means of drawing closer to Allah through various forms of righteous deeds and religious activities. This understanding is reflected in several devotional practices such as the recitation of Simṭ al-Durar and Burdah salawat, collective dhikr, communal prayers, and the commemoration of the haul (death anniversary) of respected religious scholars. These practices are perceived by the participants as spiritual media to attain blessings and strengthen their love for Prophet Muhammad (peace be upon him) and revered scholars. From the perspective of Qur’anic exegesis, these practices align with the interpretations of classical and contemporary scholars who define Wasīlah as all forms of obedience and righteous deeds that bring a servant closer to Allah. Therefore, this study demonstrates that the concept of wasīlah in QS. Al-Mā’idah verse 35 is not merely understood textually but is also actualized in the social-religious practices of the community as part of the living Qur’an phenomenon.